Measuring stakeholders' perception of Sansad Adarsh Gram Yojana - BHATTACHARYYA, SANGEETA; BURMAN, R ROY; SHARMA, J P; PADARIA, R N; PAUL, SUDIPTA; DATTA, ANINDITA; VENKATESH, P; SINGH, LAKHAN; PRASAD, Y G; NALKAR, S; KUMARI, A SARALA; RAO, N VENKATESHWAR; et al. (The Indian Journal of Agricultural Sciences, 2021)
Rural development programs act as boon to millions of rural inhabitants globally. So, it becomes extremely important for policy makers to study the perception of grassroot beneficiaries for effective implementation of ongoing program as well as plan for similar programs in future. In this study, the authors have attempted to study an ambitious rural development program named as Sansad Adarsh Gram Yojana launched by Government of India, through the lens of the beneficiaries. The program aims at adoption of villages and transforming them into Model Villages. The perception of the villagers was measured and perceived factors facilitating and inhibiting the program were identified through a multi-dimensional perception scale constructed through Principal Component Method. The study was carried out in four villages of Maharashtra and Telangana during 2018. The perception of 320 respondents when analysed, resulted in factors like Government-Public liaison (Y1=671.86), Infrastructure and Education (Y2=383.14), Local political environment (Y3=267.42), Collective power of villagers and youth (Y4=255.98), Equality (Y5=236.71) and Cultural and inherent values (Y6=143.03) facilitating the program while lack of separate funding (Y10= -12.88), bureaucratic hurdles (Y8=19.09), presence of village factions (Y9=25.05), lack of coordination among government departments (Y11=59.65) and faulty village adoption policy (Y7=130.85) hindering the progress of the program. Majority of villagers from Tikekarwadi (53.33%) of Maharashtra and from Dandepally (56.66%) of Telangana had favourable perception towards potential of the program while villagers from Inovolu (63.33%) of Telangana had neutral perception and from Malunja Budruk (80%) of Maharashtra had unfavourable perception. The classification was done on basis of Cumulative Cube Root Frequency Method (CCRF) and significant difference was found in perception scores of the respondents.